Efecto de las intervenciones no invasivas en el bienestar y la calidad de vida de los pacientes con cáncer de pulmón: resultados de una revisión sistemática - Solà, Iván; Subirana, Mireia (Psicooncología, 2006)
Aim: To highlight the results of a systematic review on the effect of non-invasive interventions delivered to lung cancer patients in improving their well-being and quality of life. Métodos: Systematic review of clinical trials assessing non-invasive interventions in lung cancer patients. Exhaustive bibliographic search in the main databases, and selection of the retrieved records to identify relevant trials on the topic. Methodological quality assessment paying special attention in randomization and allocation concealment. Heterogeneity among interventions and outcomes assessed in the included studies forced to synthesize results narratively. Results: The review identifi ed 9 clinical trials of variable quality assessing nursing programmes interventions, a nutritional intervention, counselling, an exercise programme, and refl exology. Nursing programmes to manage breathlessness seemed to have beneficial effects, as well as a nursing led assessment and follow up programme. Some counselling sessions could provide patients with skills to face simptoms better. The way to implement those interventions remains unknown. Conclusions: Implemention of multidisciplinary programmes to manage patients with lung cancer should be seriously considered. There exists the need for higher quality studies, with clear designs and methodologies that lead to stronger conclusions.